THE ANALYSIS OF FINANCIAL PERFORMANCE USING ECONOMIC VALUE ADDED (EVA) AND MARKET VALUE ADDED (MVA) METHODS AND ITS INFLUENCE ON STOCK RETURN OF TRANSPORTATION COMPANY LISTED IN INDONESIA STOCK EXCHANGE - Ira Sahara, Lia (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
This study was conducted to examine the effect of Economic Value Added (EVA) and Market Value Added (MVA) and Its Effect on Stock Return. The research sample was taken from 5 transport company listed on the Indonesia Stock Exchange that have been through the process in accordance with the criteria of sample or random sampling method. Data analysis methods used in the study panel data analysis method using Eviews program. Results showed partial EVA has no real effect, with significant values of 0.2661, while MVA and significant influence on Return Stocks with significant value of 0.0463 as indicated by the results of the test statistic t. While simultaneously or jointly Economic Value Added (EVA) and Market Value Added (MVA) influence on Stock Return, this is evidenced by the results of the test statistic f the significant value of 0.0382